THE APPLICATIONS USED FOR ONLINE LEARNING AT THE ENGLISH EDUCATION STUDY PROGRAM - Yulitriana Y; Merlyn Simbolon; Iwan Fauzi; Lisca Amelia Putri; Maria Arina Luardini; Feliks Tans (Postgraduate School, Universitas Nusa Cendana, 2020)
The pandemic of Covid-19 has forced all of the education system to switch into online, included the students and teachers of English Education Study Program, University of Palangka Raya. This research is intended to analyze the use of applications by students and teachers, also the reasons of using the applications. This research applied qualitative method and the data were analyzed descriptively. The data were the responses from teachers and students for the questionnaires given through Google Forms. The subjects for gaining the data were the students of academic year 2020/2021 and the teachers at the English Education Study Program, the Faculty of Teacher Training and Education, University of Palangka Raya. The results show that the five most favourite applications used by the students were Google Classroom (85.97%), Zoom (74.66%), WhatsApp (48.41%), Google Meet (47.51%), YouTube (11.76%). The reasons why the students used the applications were the applications were easy to use (77.77%), they were quota saving (25%), they were easy to access (11.11%), they had many features (11.11%), and they were effective (9.25%). The five applications used by most of the teachers at the English Education Study Program were Google Classroom (88.88%), Zoom (61.11%), WhatsApp (50%), Google Meet (38.88%), Google Form (22.22%). The reasons why they chose the applications were because the applicationswere easy to use (66.66%), the familiarity with the application (22.22%) and they were easy to access/connection friendly (22.22%). The additional reasons were the applications were quota saving (16.66%), it had complete features (16.66%) and they were unlimited (16.66%). The reasons that both students and teachers gave in this research regarding the applications used in online learning can be the considerations, especially for the teachers and the institution in designing and choosing the best applications, platforms, or teaching tools for the online learning